Cordierite thermal insulation materials reinforced by aluminosilicate fiber/mullite whiskers hierarchical structure. Issue 4 (31st January 2018) - Qin, Meng Li; Wang, Xi Tang; Wang, Zhou Fu; Ma, Yan; Liu, Hao
Abstract: Cordierite thermal insulation materials were prepared via a starch consolidation casting (SCC) technique, using kyanite, MgO and SiO2 as raw materials. Aluminosilicate ceramic fiber were used as the substrate for in situ synthesized mullite whiskers. The mullite whiskers grew in situ on the surface of the aluminosilicate ceramic fiber via AlF3 and were interspersed among the cordierite crystalline. The as‐prepared cordierite materials reinforced by the aluminosilicate ceramic fiber/mullite whiskers hierarchical structure had a relatively high cold modulus strength and cold compression strength. Moreover, the thermal conductivity of the materials was as low as 0.329 W/(m K) (RT‐1000°C). We propose a growing mechanism of mullite whiskers on the surface of the aluminosilicate ceramic fiber.